Staging creolization : women's theater and performance from the French Caribbean - Sahakian, Emily (New World studies., 2017)
"Emily Sahakian examines plays by Ina Césaire, Maryse Condé, Gerty Dambury, and Simone Schwarz-Bart that premiered in the French Caribbean or in France in the 1980s and 1990s and soon thereafter traveled to the United States. Sahakian argues that these late-twentieth-century plays by French Caribbean women writers dramatize and enact creolization -- the process of cultural transformation through mixing and conflict that occurred in the context of the legacies of slavery and colonialism"--